FAKTOR-FAKTOR YANG MEMPENGARUHl MAHASlSWA AKUNTANSl TERHADAP PEMlLlHAN KARIR (Studi Empiris pada Mahasiswa Akuntansi Universitas Muhammadiyah Metro) - M Aryant Wahyu Pratama; Jawoto Nusantoro; Ana Septiani (Jurnal Akuntansi AKTIVA, 2021)
This study aims to examine the factors that influence accounting students on career choices. The population in this study were undergraduate accounting students who are currently or have completed their thesis final assignments with a population of 74 students. This study uses a quantitative approach. The data used in this study are primary data obtained directly from research subjects in the form of a questionnaire with a Likert scale data measurement tool. The data analysis technique used is multiple linear regression and was performed with the help of IBM SPSS Version 25.0. The results showed that all factors that influence student career choices, namely work environment, professional training, social values, personality, job intrinsic values, job market considerations and professional recognition have a significant effect on student career choices.